PENGARUH PERSON-ORGANIZATION FIT TERHADAP KOMITMEN ORGANISASIONAL MELALUI KEPUASAAN KERJA PADA KARYAWAN IBI DARMAJAYA - stefanus rumangkit; Sri Maryati (Universitas Ahmad Dahlan, 2017)
This study aims to examine the influence of person organization fit on organizational commitment with work satisfaction as a mediator variable. The data collected as many as 150 respondents obtained from educative employees Institute of Informatics and Business Darmajaya in the years of 2017. From the data obtained, then performed data analysis using the regression model of mediation through a simple regression analysis and multiple regression method. The results of this study indicate that the person organization fit has a positive and significant effect on organizational commitment. From the results of this study can be reported that the socialization of the organization have a positive and significant impact on the suitability of values. Other findings from this study indicate that conformity values have a positive and significant effect on affective commitment. In addition, the results of this study also indicate that conformity values mediate the effect of organizational socialization on affective commitment.